Successful autologous hematopoietic stem cell transplantation in a refractory anti‐Caspr1 antibody nodopathy - Afanasiev, Vadim; Tsouni, Pinelopi; Kuntzer, Thierry; Cairoli, Anne; Delmont, Emilien; Vallat, Jean‐Michel; Devaux, Jérôme; Théaudin, Marie (Journal of the peripheral nervous system, 2024)
Aim Autoimmune nodopathies have specific clinicopathologic features, antibodies directed against nodal proteins (neurofascin 186) or paranodal proteins (neurofascin 155, contactin 1, contactin‐associated protein 1 (Caspr1)), and usually have a poor response to first‐line therapies for chronic inflammatory demyelinating polyradiculoneuropathy. Anti‐Caspr1 nodopathy treated with autologous hematopoietic stem cell transplantation (AHSCT) has not been previously reported. Methods We report the first case of an anti‐Caspr1 antibody‐positive nodopathy refractory to high‐intensity immunosuppressive treatment, including rituximab, that responded dramatically to AHSCT. Results A 53‐year‐old woman presented with a rapidly progressive generalized ataxic, painful motor, and inflammatory neuropathy supported by neurophysiologic and MRI studies. Initial tests for antibodies to nodal/paranodal proteins were negative. She was treated with multiple courses of intravenous immunoglobulin and methylprednisolone, plasma exchange, rituximab, and cyclophosphamide without significant clinical benefit. Repeated testing for antibodies to nodal/paranodal proteins yielded a positive result for anti‐Caspr1/IgG4 isotype antibodies. Given the poor response to multiple high intensity treatments and the relatively young age of the patient, we decided to perform AHSCT at 30 months post‐onset. Immediately after AHSCT, she stopped all immunomodulatory or immunosuppressive therapy. The Overall Neuropathy Limitation Score improved from 8/12 to 4/12 at 6 months post‐AHSCT. At 3 months post‐AHSCT, IgG4 against Caspr1 was negative and no reactivity against paranodes could be detected. Conclusion We report a particularly severe anti‐Caspr1 antibody autoimmune nodopathy that responded dramatically to AHSCT. Although the rarity of the disease limits the possibility of larger studies, AHSCT may be a valuable therapy in treatment‐refractory cases.